2022
DOI: 10.1039/d2dt00422d
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the coordination approach of Eu(iii) in cyphos nitrate ionic liquid – a comprehensive luminescence spectroscopy study

Abstract: In consideration of the mounting attention of the ionic liquid: Cyphos 101 (trihexyl(tetradecyl)phoshonium chloride: [P66614][Cl]) in the recovery of rare earth and other valuables from their waste matrices, an effort...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The synthesis and structural characterization of periodic series of rare earth complexes with halides, pseudo-halides and oxoacids represents a particularly fruitful area for exploration of rare earth chemistry provided the applications of these materials in rare earth separations, recycling, molecular and materials synthesis. These species are utilized in the synthesis of a broad spectrum of rare earth containing molecules and materials, such as emitters in luminescent materials, [5][6][7][8][9][10] anions in functional ionic liquids, [11][12][13][14][15][16][17] and are components of many other compounds with useful magnetic and material properties. [18][19][20][21][22][23][24] When crystallized in the presence of weakly Lewis-acidic cations such as alkali metal cations, trivalent rare earth nitrate salts typically take the form of 10-or 12-coordinate anionic penta-or hexanitrato complexes in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and structural characterization of periodic series of rare earth complexes with halides, pseudo-halides and oxoacids represents a particularly fruitful area for exploration of rare earth chemistry provided the applications of these materials in rare earth separations, recycling, molecular and materials synthesis. These species are utilized in the synthesis of a broad spectrum of rare earth containing molecules and materials, such as emitters in luminescent materials, [5][6][7][8][9][10] anions in functional ionic liquids, [11][12][13][14][15][16][17] and are components of many other compounds with useful magnetic and material properties. [18][19][20][21][22][23][24] When crystallized in the presence of weakly Lewis-acidic cations such as alkali metal cations, trivalent rare earth nitrate salts typically take the form of 10-or 12-coordinate anionic penta-or hexanitrato complexes in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the AR values were evaluated from the intensity ratio (I 615 /I 592 ) of the electric dipole transition to the magnetic dipole transition instead of the area (A 2 /A 1 ) under two peaks, as described 24 These exercises revealed that the solvent extraction results of lanthanides cannot always be correlated with its fluorescence behavior as described elsewhere, and it absolutely depends on the nature of the extractant system and the nature of co-extracting metal ions present along with Ln(III). 26 It has been further clarified with Pd(II)/Eu(III) luminescence results (vide infra). Another reason for the peak intensity enhancement in the presence of Zr(IV) could be ascribed to the co-extraction of NO 3…”
Section: Eu(iii) Emission In the Presence Of Zr(iv)mentioning
confidence: 93%
“…FLS-920). 26,27 A fused silica cuvette of 2 mm path length was used for the sample accommodating cell, while a fixed bandpass of 2 nm was employed for the excitation and emission monochromators. For suppressing the scattering effect of the incident beam projected to the monochromator, a long-wavelength pass filter (UV -39, Shimadzu), having a uniform transmittance of 485% above 400 nm, was assimilated ahead of the emission monochromator.…”
Section: Instrumental Detailsmentioning
confidence: 99%
See 2 more Smart Citations